How we do it: whole lung lavage : Whole lung lavage - Shreshta, Deepa; Dhooria, Sahajal; Munirathinam, Ganesh Kumar; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Ram, Babu; Singh, Harkant; Aggarwal, Ashutosh Nath; Puri, Goverdhan D; Muthu, Valliappan; Agarwal, Ritesh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Pulmonary alveolar proteinosis (PAP) is a rare pulmonary disorder characterized by the accumulation of surfactant in the alveolar spaces resulting in hypoxemic respiratory failure. Whole lung lavage (WLL), the preferred treatment for PAP, physically removes the lipo-proteinaceous material from the alveolar spaces. Since its initial description in 1963, the WLL procedure has undergone various modifications. However, the procedure has not been standardized yet. After securing a double lumen endotracheal tube, we perform WLL under general anesthesia. One lung is ventilated, while the other is lavaged using one-liter aliquots of pre-warmed saline. We use gravity-assisted drainage of the lavaged lung after each cycle till the milky white and opaque fluid becomes clear (usually 15-20 cycles). Herein, we describe the step-by-step procedure, precautions, and monitoring of WLL. We also provide videos demonstrating one-lung ventilation and bronchoscopic confirmation of lung isolation. Keywords: Pulmonary alveolar proteinosis; bronchoscopy; bronchoalveolar lavage; interstitial lung disease: diffuse parenchymal lung disease